Overexpression of soybean trypsin inhibitor genes decreases defoliation by corn earworm (Helicoverpa zea) in soybean (Glycine max) and Arabidopsis thaliana - Sultana, Mst Shamira; Mazarei, Mitra; Jurat-Fuentes, Juan Luis; Hewezi, Tarek; Millwood, Reginald J.; Stewart, C. Neal (Frontiers in Plant Science, 2023)
Trypsin inhibitors (TIs) are widely distributed in plants and are known to play a protective role against herbivores. TIs reduce the biological activity of trypsin, an enzyme involved in the breakdown of many different proteins, by inhibiting the activation and catalytic reactions of proteins. Soybean (Glycine max) contains two major TI classes: Kunitz trypsin inhibitor (KTI) and Bowman-Birk inhibitor (BBI). Both TI genes inactivate trypsin and chymotrypsin enzymes, which are the main digestive enzymes in the gut fluids of Lepidopteran larvae feeding on soybean. In this study, the possible role of soybean TIs in plant defense against insects and nematodes was investigated. A total of six TIs were tested, including three known soybean trypsin inhibitors (KTI1, KTI2 and KTI3) and three genes encoding novel inhibitors identified in soybean (KTI5, KTI7, and BBI5). Their functional role was further examined by overexpression of the individual TI genes in soybean and Arabidopsis. The endogenous expression patterns of these TI genes varied among soybean tissues, including leaf, stem, seed, and root. In vitro enzyme inhibitory assays showed significant increase in trypsin and chymotrypsin inhibitory activities in both transgenic soybean and Arabidopsis. Detached leaf-punch feeding bioassays detected significant reduction in corn earworm (Helicoverpa zea) larval weight when larvae fed on transgenic soybean and Arabidopsis lines, with the greatest reduction observed in KTI7 and BBI5 overexpressing lines. Whole soybean plant greenhouse feeding bioassays with H. zea on KTI7 and BBI5 overexpressing lines resulted in significantly reduced leaf defoliation compared to non-transgenic plants. However, bioassays of KTI7 and BBI5 overexpressing lines with soybean cyst nematode (SCN, Heterodera glycines) showed no differences in SCN female index between transgenic and non-transgenic control plants. There were no significant differences in growth and productivity between transgenic and non-transgenic plants grown in the absence of herbivores to full maturity under greenhouse conditions. The present study provides further insight into the potential applications of TI genes for insect resistance improvement in plants.